SMART-system: A Japanese Innovation - Miyaji, C. (5. International Forum on Elite Sport. Beijing, China, 3-6 September 2007, 2007)
The SMART-system enables to… - Keep personal training history - Share videos with coaches and athletes - Create archives for big competitions - Create educational contents for the movements … and more applications